Plasma ghrelin responses to prolonged sculling in male competitive rowers - Purge, P.; Jürimäe, J.; Rämson, R.; Mäestu, J.; Jürimäe, T.; von Duvillard, S. P. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The aim of the present investigation was to investigate plasma ghrelin responses to a single endurance rowing training session in male comüpetitive single scull rowers. Nine national standard male rowers (20.1±1.5 years, 183.9±4.3 cm, 81.0±5.0 kg, body fat%: 10.8±3.3%) volunteered for this study. The participants completed two 2.5 h trials (exercise or control) on separate days. The exercise trial involved a prolonged rowing training session lasting about 2 h (7373±129 s, distance covered 20.7±1.4 km, heart rate 133±4 bpm, intensity 80.2±1.6% of anaerobic threshold) followed by 30 min rest. The control trial consisted of 2.5 h of rest. Venous blood samples were obtained at 0, 2.0 and 2.5 h. No differences were found between baseline values for measured plasma ghrelin and leptin concentrations at exercise and control trials. Plasma ghrelin concentration was increased (+12.2%; P<0.05) and leptin concentration decreased (-20.0%; P<0.05) after the first 30 min of recovery at exercise trial. No differences in plasma ghrelin or leptin concentrations over time were observed during control trial. There were no relationships between basal ghrelin concentration and the measured body composition, energy balance, physical performance, or blood biochemical data. Plasma ghrelin (r=0.75) concentration measured immediately after the training session were related (P<0.05) to the distance covered, but no such relation was observed for post-exercise leptin concentration (r=-0.16; P>0.05). In conclusion, these results suggest that acute negative energy balance induced by a single prolonged endurance rowing training session elicits a metabolic response with opposite changes in ghrelin concentrations in competitive male rowers.